2004
DOI: 10.1063/1.1805200
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous-to-crystal transition of nitrogen- and oxygen-doped Ge2Sb2Te5 films studied by in situ resistance measurements

Abstract: The amorphous-to-crystal transition has been studied through in situ resistance measurements in Ge2Sb2Te5 thin films doped by ion implantation with nitrogen or oxygen. The dependence of the electrical resistivity and structure on the annealing temperature and time has been investigated in samples with different dopant concentrations. Enhancement of the thermal stability and increase of the mobility gap for conduction have been observed in O- and N-doped amorphous Ge2Sb2Te5. Larger effects have been found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(128 citation statements)
references
References 9 publications
(8 reference statements)
5
123
0
Order By: Relevance
“…The higher temperature used for N-GST is due to increasing of the crystallization temperature for GST after N doping. 7,16,17 RESULT AND DISCUSSION Figure 1 shows the resistance as a function of time measured at 140°C in an undoped GST film. The as-deposited sample was amorphous.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The higher temperature used for N-GST is due to increasing of the crystallization temperature for GST after N doping. 7,16,17 RESULT AND DISCUSSION Figure 1 shows the resistance as a function of time measured at 140°C in an undoped GST film. The as-deposited sample was amorphous.…”
Section: Methodsmentioning
confidence: 99%
“…It indicated that N-GST was also crystallized layer by layer and it is in agreement with observation on ion-implanted N-doped sample. 16 By resistance measurement and an analysis procedure similar to GST, we also got the JMAK parameters of N-GST. Figure 4 is the result of the sample annealed at 165°C and the plot of ln͑−ln͕͑ c − ͒ / ͓ c − ͑ ͔͖͒͒ as a function of ln͑tЈ͒ is a straight line with slope of 1.59 ͓Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations